(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Ovarian disease is the most common disease occurring in female reproductive organs. The premature recognition and action needed for diagnosis the disease to avoid infertility or cancer to them. The reason behind infertility is Polycystic Ovary Syndrome (PCOS) and the Ovarian Regenerative Tissues Cells.Â PCOS is the kind of endocrine disorder present in femaleâ€™s ovary and creates problem with Irregular menstrual periods, skin diseases, excess hair growth in body and face, acne and finally infertility. For ovarian regenerative tissues cells histopathology slides can be well stored put away in digitized color image design. One of the well known determination inclinations to recognize ovarian tissues is ultrasound image scanner. In any case, because of various shape, size and color, distinguishing proof of ovarian tissues is a testing assignment for ultrasound scanners as it procedure dark scale images. In order to overcome these diseases, we proposed techniques for ultrasound images. By this techniques follicle in the ovary and the ovarian regenerative tissues cells is automatically detected.